2017
DOI: 10.12659/msm.900252
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Femur and Femoral Arteries for Identifying Risk Factors for Vascular Injury

Abstract: BackgroundThis study aimed to identify risk factors for vascular injury in proximal femoral fracture through identifying frequency and distances between femur and femoral arteries with computed tomography angiography and 3-dimensional reconstruction.Material/MethodsIn a series of 400 participants, based on measurement results regarding the distribution of femoral arteries in the medial femur, the femoral portion covering that part was divided into levels A–E. The center region, margin region, and risky area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Надмірні навантаження на суглобові поверхні, як поодинокі (гострий вплив), так і повторювані (кумулятивне контактне напруження), можуть викликати зміни в суглобовому хрящі та розвиток остеоартозу як наслідок прямої травми на колінний суглоб [4]. Посттравматичний остеоартрит, як результат травми суглоба, викликає у багатьох мільйонів людей біль протягом усього життя і призводить до інвалідності [5][6][7][8][9][10].…”
Section: Results An Articular Cartilage Of the Proximal Tibial Epiphunclassified
“…Надмірні навантаження на суглобові поверхні, як поодинокі (гострий вплив), так і повторювані (кумулятивне контактне напруження), можуть викликати зміни в суглобовому хрящі та розвиток остеоартозу як наслідок прямої травми на колінний суглоб [4]. Посттравматичний остеоартрит, як результат травми суглоба, викликає у багатьох мільйонів людей біль протягом усього життя і призводить до інвалідності [5][6][7][8][9][10].…”
Section: Results An Articular Cartilage Of the Proximal Tibial Epiphunclassified
“…Understanding the anatomical relationship between the femur and femoral artery along with its branches is critical in preventing iatrogenic vascular injuries. Sun et al showed that the femoral artery along the medial side of the femur, especially PFA and deep femoral artery, were at a higher risk of injury as they lay within 13 mm of bone [ 9 ]. The femoral artery on the medial side of the femur was at risk to screw insertion or overshooting with the drill.…”
Section: Discussionmentioning
confidence: 99%
“…A small part of these complications is related to the surgical procedure itself, as infection and loss of reduction. Vascular injuries are not common, but they are of great importance, because they may be potentially life or limb-threatening [ 1 , 2 ]. The deep femoral artery is the most commonly affected branch in the upper part of the femur (about 78.31 %).…”
Section: Discussionmentioning
confidence: 99%
“…Other possible factors that may also predispose to arterial injury are the use of an oversize perineal pole, excessive traction, or positioning the limb in adduction and internal rotation. This position forces the deep femoral artery and its branches to be near the medial aspect of the sub-trochanteric femur, making them vulnerable to injury by fracture fragments or screws [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%